Under risk, over time, regarding other people: Language and rationality within three dimensions - Dorian Jullien (Duke University, Center for the History of Political Economy (CHOPE), 2018)
This paper conducts a systematic comparison of behavioral economics's challenges to the standard accounts of economic behaviors within three dimensions: under risk, over time and regarding other people. A new perspective on two underlying methodological issues, i.e., interdisciplinarity and the positive/normative distinction, is proposed by following the entanglement thesis of Hilary Putnam, Vivian Walsh and Amartya Sen. This thesis holds that facts, values and conventions have interdependent meanings in science which can be understood by scrutinizing formal and ordinary language uses. The goal is to provide a broad and self-contained picture of how behavioral economics is changing the mainstream of economics.
Keywords: A12; B21; B41; D01; D03; D81; D90; D64; 330; behavioral economics; economic rationality; expected utility; prospect theory; exponential discounting; hyperbolic discounting; self-interest; other-regarding behaviors; economic methodology; history of economics; philosophy of economics; economics and language